Circulating tumour cells & circulating tumour DNA in patients with resectable colorectal liver metastases (MIRACLE): a prospective, observational biomarker studyResearch in context - Lissa Wullaert; Maurice P.H.M. Jansen; Jaco Kraan; Yannick M. Meyer; Kelly Voigt; Stavros Makrodimitris; Vanja de Weerd; Corine M. Beaufort; Mai Van; Maarten Vermaas; Eric J.T. Belt; Paul D. Gobardhan; et al. (EClinicalMedicine)
Summary: Background: Recurrence risk after curative surgery for colorectal liver metastases (CRLM) remains high, underlining the need to identify prognostic markers enabling more individualised treatment approaches. Methods: In the MIRACLE, a prospective, observational biomarker study, a total of 188 patients with isolated, resectable CRLM without (neo)adjuvant chemotherapy were included between October 2015 and December 2021. Blood samples were collected before surgery (baseline) and three weeks after surgery. The primary objective was to assess the potential association between postoperative circulating tumour DNA (ctDNA) detection and recurrence of disease for patients with resectable CRLM within one year after resection. The secondary objective was the association between recurrence of disease within one year and detection of circulating tumour cells (CTCs). Baseline ctDNA was measured by next generation sequencing using a targeted panel (Oncomine Colon cell-free DNA assay) and postoperatively by digital PCR on genetic variants found preoperatively with the Oncomine panel. CTCs were enumerated using the FDA-approved CellSearch system. Findings: ctDNA was detected in 117/187 patients (63%) at baseline, and 28/104 evaluable patients (27%) still had detectable ctDNA postoperatively. CTC enumeration resulted in positivity for 37/183 patients (20%) at baseline and 14/158 patients (9%) postoperatively. No association was found between 1-year recurrence-free survival (RFS) and the presence of CTCs or ctDNA at baseline. In contrast, patients with postoperative undetectable ctDNA had a significantly improved 1-year RFS compared to patients with postoperative ctDNA (54% [95% CI 44%–67%] vs. 25% [95% CI 13%–47%], log-rank p = 0.0011). Similarly, patients with postoperative detectable CTCs had a significantly shorter 1-year RFS compared to patients without postoperative CTCs (15% [95% CI 4%–55%] vs. 53% [95% CI 45%–62%], log-rank p 0.0004). Also in multivariable analysis, detectable ctDNA and CTCs after surgery remained independently associated with a shorter 1-year RFS (HR 2.35; 95% CI 1.34–4.11; p = 0.0028 and HR 2.98; 95% CI 1.56–5.71; p = 0.0010, respectively). Interpretation: This is the first study conducted in patients with resectable CRLM without (neo)adjuvant chemotherapy, which demonstrates the impact of postoperative detectable circulating tumour load on 1-year RFS. Postoperative ctDNA and CTC detection both represent strong, independent predictors for a shorter RFS after local treatment, as opposed to preoperative detection. Funding: This work was supported by KWF Kankerbestrijding (Dutch Cancer Society, EMCR 2014-6340).